Studi Pemanfaatan Canva dalam Digitalisasi Budaya Nusantara sebagai Media Edukasi dan Dokumentasi bagi Siswa PKBM ADAM Kubu Raya - Agersi Diah Anggraini (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Cultural digitalization serves as a strategic move in the era of globalization to prevent the erosion of the Indonesian archipelago's cultural heritage among the younger generation. This Community Service (PkM) activity aimed to enhance students' digital literacy skills The ADAM Community Learning Center (PKBM) in Kubu Raya conducted a workshop on utilizing Canva to digitize the archipelago's culture, serving as a medium for both education and cultural documentation. A participatory engagement approach was employed, combining interactive lectures, guided hands-on practice, and intensive mentoring for 30 students enrolled in equivalency education programs (Packages A, B, and C). Cognitive evaluation results demonstrated a significant improvement in understanding, with the average score rising from 56.67 (pre-test) to 86.33 (post-test) and an N-Gain score of 0.68 (moderate category). Regarding psychomotor skills, the assessment of students' independent projects fell into the "good" category, with an average feasibility score of 85.41%. Furthermore, a positive behavioral shift was observed; students became active creators of local cultural content using their mobile devices. The activity also fostered participants' awareness regarding the importance of cultural preservation through digital media. Thus, the workshop proved effective in enhancing digital literacy while simultaneously supporting the preservation of the archipelago's culture in a creative and sustainable manner.